The art of the possible : an everyday guide to politics - Keenan, Edward (Owlkids Books, 2015)
An introduction to politics, and why we need them. Includes topics such as why we form societies, the basic types of governments, the power of public opinion, methods of rhetoric, and the reasons why politicians 'lie'.